2019
DOI: 10.1088/1361-6595/aae554
|View full text |Cite
|
Sign up to set email alerts
|

Transition mechanism of negative DC corona modes in atmospheric air: from Trichel pulses to pulseless glow

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Charged particles dynamics are modeled by drift-diffusion equations [18][19][20]. + n e ν i − S r e−p − S r n−p , (1.2) ∂n n ∂t = ∇ • (D n ∇n n ) + ∇ • (v air + μ n En n ) + n e ν a − S r n−p , (1.3) where n e , n p , and n n are the densities of electrons, positive ions and negative ions and E is the electric field vector.…”
Section: Physical Modelmentioning
confidence: 99%
“…Charged particles dynamics are modeled by drift-diffusion equations [18][19][20]. + n e ν i − S r e−p − S r n−p , (1.2) ∂n n ∂t = ∇ • (D n ∇n n ) + ∇ • (v air + μ n En n ) + n e ν a − S r n−p , (1.3) where n e , n p , and n n are the densities of electrons, positive ions and negative ions and E is the electric field vector.…”
Section: Physical Modelmentioning
confidence: 99%
“…In [13], Kurimoto and Farish found that the gas temperature of negative pulseless glow in air is ∼500-900 K. The heat is transferred to the surrounding region by air convection. Chen et al [19] showed that gas heating plays a more important role on the transition process than the detachment of negative ions. In [27], the gas temperature of pulsed positive coronas in atmospheric air was measured.…”
Section: Discussionmentioning
confidence: 99%
“…At higher humidity, the vibrational-translational (V-T) collision rates of H 2 O-O 2 , H 2 O-N 2 and H 2 O-H 2 O are significantly enhanced, so the energy transfer between O 2 and N 2 to the translational energy is accelerated, resulting in an increase in gas temperature. When the gas temperature increases, the gas number density decreases and the reduced electric field (E/N) increases [19]. The electron impact ionisation increases significantly, and the drift velocity of charged particles is also increased, which can expedite the transition process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Thus, in the case of a pulsed corona, time-dependent solvers, while being an adequate tool for studies of spatiotemporal evolution of individual pulses (e.g., Refs. [31][32][33][34][35], cannot be used for the direct calculation of time-averaged characteristics of the discharge. The latter can be conveniently computed by means of stationary solvers in the framework of the integrated approach being used in this section.…”
Section: B Coaxial and Point-to-plane Corona Dischargesmentioning
confidence: 99%